2019
DOI: 10.1039/c9cy01351b
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanisms at the homogeneous–heterogeneous frontier: insights from first-principles studies on ligand-decorated metal nanoparticles

Abstract: The frontiers between homogeneous and heterogeneous catalysis are progressively disappearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 205 publications
(209 reference statements)
0
48
0
Order By: Relevance
“…However, there are intrinsic challenges to studying such metal-ligand interfaces. 30 Most DFT studies on reaction mechanisms on MPCs have been carried out on ligand-decorated metal surface models due to the computational limitations in studying large number of atoms. Models with classical force fields would significantly speed up simulations, but the variety of bonds within the MPCs make fitting of parameters demanding and reliable modeling of chemistry (making and breaking bonds) with classical force fields is still largely an unsolved challenge.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are intrinsic challenges to studying such metal-ligand interfaces. 30 Most DFT studies on reaction mechanisms on MPCs have been carried out on ligand-decorated metal surface models due to the computational limitations in studying large number of atoms. Models with classical force fields would significantly speed up simulations, but the variety of bonds within the MPCs make fitting of parameters demanding and reliable modeling of chemistry (making and breaking bonds) with classical force fields is still largely an unsolved challenge.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of synthetic methods and organic molecules (surfactants, organic ligands based on C, N, P, S or O atoms) have been adopted to functionalize metal NPs. 416 Thiols, amines and NHC ligands represent the main families of organic ligands used to stabilize monometallic NPs for CO 2 RR, and the main advances for each class are discussed in the next paragraphs. NPs or NCs based on late transition metals, such as Au, Ag and Pd, cover the overwhelming majority of the reported organic-stabilized nanocatalysts for CO 2 RR, generally producing CO as the major product.…”
Section: Surface Functionalization With Organic Moleculesmentioning
confidence: 99%
“…1 ). 46 48 For example, recent study demonstrated significant impact of the NHC ligand structure on the catalytic activity of Pd/Al 2 O 3 heterogeneous catalysts composed of NHC–ligated Pd nanoparticles in bromobenzene hydrogenolysis and Buchwald–Hartwig amination of aryl halides. 46 Comparative DFT calculations for neat and NHC–ligated Pd 13 clusters revealed that coordinated NHCs convey electron density to nanoclusters thus lowering the energy barriers of aryl halide oxidative addition.…”
Section: State-of-the-art Catalysis By Metal Complexes With Nhc Liganmentioning
confidence: 99%